Vasopressin induced hyponatremia in infants <3 months of age in the neonatal intensive care unit - Patel, Kavita; Thomson, Sharon; Vijayan, Meera; Makoni, Marjorie; Johnson, Peter N.; Stephens, Katy; Neely, Stephen B.; Miller, Jamie L. (Frontiers in Pediatrics, 2024)
Objectives: Vasopressin is used for shock and acute pulmonary hypertension in the neonatal intensive care unit (NICU) and is associated with hyponatremia. The purpose of this study was to determine the incidence, severity, contributing risk factors associated with vasopressin-induced hyponatremia in neonates and infants <3 months of age in the NICU. The primary objective was to determine the incidence of hyponatremia (<130 mEq/L) and severe hyponatremia (< 125 mEq/L). The secondary objectives were to compare clinical characteristics and the vasopressin regimen between those with and without hyponatremia.Methods: This retrospective cohort study included neonates and infants <3 months from 1/1/2017-12/31/2022 receiving vasopressin for >6 hours. Analyses were performed using SAS v9.4, with a priori less than 0.05. A multiple variable logistic regression was employed to assess odds of hyponatremia.Of the 105 patients included, 57 (54.3%) developed hyponatremia, and 17 (29.8%) were classified as severe hyponatremia. Overall, the median (interquartile range, IQR) gestational and postnatal age at vasopressin initiation were 35.4 (27-38.7) weeks and 2 (1-12) days. There was no difference in vasopressin dose, but duration of treatment was longer in those with hyponatremia. Higher baseline serum sodium was associated with decreased odds of hyponatremia [adjusted odds ratio (OR): 0.90 (95% CI: 0.83-0.99), p=0.03], and increased vasopressin duration was associated with increased odds of hyponatremia [aOR: 1.02 (95% CI:1.01-1.03), p<0.001].Conclusions: Hyponatremia occurred in half of patients included. The pre-vasopressin sodium value and the vasopressin duration were independently associated with hyponatremia.